Long‐term outcomes of surgery followed by radiation therapy for minor salivary gland carcinomas. (1st April 2013) - Zeidan, Youssef H.; Shultz, David B.; Murphy, James D.; An, Yi; Chan, Cato; Kaplan, Michael J.; Colevas, A. Dimitrios; Kong, Christina; Chang, Daniel T.; Le, Quynh‐Thu
Abstract : Objectives/Hypothesis: Postoperative radiation therapy is often used in patients with high‐risk salivary gland carcinomas. In this study we evaluated the outcomes and prognostic factors in patients with minor salivary gland cancers treated with adjuvant radiation therapy. Study Design: Retrospective cohort study. Methods: We performed a retrospective analysis of 90 patients treated with curative intent. Median follow‐up was 71 months. Fifty‐eight patients (64%) had adenoid cystic carcinomas, 22 (24%) had adenocarcinomas, and 10 (11%) had mucoepidermoid cancers. Primary disease site included 39 (43%) sinonasal, 35 (39%) oral cavity, 10 (11%) oropharynx, and six (7%) others. Twenty‐seven patients (30%) were treated with intensity‐modulated radiation therapy. Results: Eight local, four neck, and 24 distant relapses were detected. Local control rates at 5 and 10 years were 90% and 88%, respectively. Advanced T stage was associated with worse local control. Distant metastasis rates were 24% and 28% at 5 and 10 years, respectively. Tumor stage, histology, perineural invasion, and lymphovascular space invasion were significant predictors of distant metastasis on univariate analysis. However, on multivariate analysis only the American Joint Committee on Cancer stage was significant. Overall survival rates were 76% and 63% at 5 and 10 years, respectively. More advanced T stage and N stage correlated with worse overall survival. Conclusions: Tumor stage remains the best predictor for locoregional and distant disease control of minor salivary gland cancers. Postoperative radiation therapy for high‐risk patients results in excellent long‐term locoregional disease control. Further work is needed to improve systemic control. Level of Evidence: 4. Laryngoscope, 123:2675–2680, 2013